1999
DOI: 10.2307/3579934
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Silicon Microdosimetry Detectors in Boron Neutron Capture Therapy

Abstract: Reverse-biased silicon p-n junction arrays using Silicon-On-Insulator technology have been proposed as microdosimeters. The performance of such detectors in boron neutron capture therapy (BNCT) is discussed. This work provides the first reported measurements using boron-coated silicon diode arrays as microdosimeters in BNCT. Results are in good agreement with measurements with gas proportional counters. Various boron-coating options are investigated along with device orientation effects. Finally, a 235U coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…17,18 This device has also been used extensively in hadron and proton therapy, particularly in primary beam microdosimetry measurements. 16,17,[19][20][21] In this experimental setup, the SOI microdosimeter, preamplifier, and accompanying electronics were situated within an aluminum probe assembly to allow for a low noise environment to be achieved. The wall thickness of the probe was 900 m, with a 4 m aluminum window immediately in front of the microdosimeter to allow for the transport of low range secondaries into the microdosimeter.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 This device has also been used extensively in hadron and proton therapy, particularly in primary beam microdosimetry measurements. 16,17,[19][20][21] In this experimental setup, the SOI microdosimeter, preamplifier, and accompanying electronics were situated within an aluminum probe assembly to allow for a low noise environment to be achieved. The wall thickness of the probe was 900 m, with a 4 m aluminum window immediately in front of the microdosimeter to allow for the transport of low range secondaries into the microdosimeter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Such converters have been employed in previous neutron and mixed field measurements with this device. 17,20 All measurements were completed using a patient specific aperture-bolus combination, and proton energy of 225 MeV to simulate a typical radiation field delivered in a clinical prostate case. The maximum aperture diameter was 8 cm both in lateral and vertical direction.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As previously reported [2], [3], [5], the SOI microdosimeter consists of an array of reversed biased, p-n junctions as illustrated in Figs. 1 and 2.…”
Section: B Soi Microdosimeter Descriptionmentioning
confidence: 99%
“…Silicon microdosimetry studies using SOI devices in radiation oncology have been reported previously [2]- [5]. In these studies, silicon microdosimeters were used to measure lineal energy spectra in such radiation oncology modalities as boron-neutron capture therapy (BNCT) [3], [4] and Proton therapy [2]. Recently the technique has been applied to measurements in fast neutron therapy (FNT).…”
mentioning
confidence: 99%
“…The Centre for Medical Radiation Physics (CMRP) has developed three generations of microdosimeters based on silicon-on-insulator (SOI) substrates [4][5][6][7][8]. These SOI microdosimeters were based on planar and pseudo 3D mesa rectangular parallelepiped (RPP) and cylindrical SVs produced on p-SOI and n-SOI using diffusion or implantation techniques for forming laterally depleted p-i-n diodes.…”
mentioning
confidence: 99%